Identifikasi Penyebab Rendahnya Kepesertaan JKN pada Pekerja Sektor Informal di Kawasan Pedesaan - Wahyu Kurniawati; Riris Diana Rachmayanti (Indonesian Journal of Health Administration (Jurnal Administrasi Kesehatan Indonesia), 2018)
The low membership of National Health Insurance (NHS) with only 56.85% family owning JKN Card was identified as the main problem based on urgency, seriousness, and growth in Payaman Village, Ngraho Sub-district, Bojonegoro District,. The purpose of this study is to identify the root cause of low JKN’s membership by using Fishbone Analysis. This study was a Cross-sectional study. The sample in this research was 204 families selected by using simple random sampling technique. Data collection was conducted with interviews and direct observation. The root causes of the problems are the low level of public knowledge, lack of socialization, low level of education, and lack of health promotion media. The head of the family is less aware of the importance of NHS. Efforts that can be done by the village management in cooperation with Pondok Kesehatan Desa (Ponkesdes) Payaman Village and Badan Penyelenggara Jaminan Sosial(BPJS) Bojonegoro District are to educate the community about the importance of JKN card ownership, increase the availability of socialization media to make  easier in understanding JKN, and form JKN cadres in Payaman Village. Keywords : worker, informal, rural, national health insurance, fishbone